El deterioro cognitivo en un paciente con insuficiencia renal que realiza hemodiálisis - Espinoza Chávez, Daniela Milena (2020)
This present research work has the theme "Cognitive deterioration in a patient with renal insufficiency who performs hemodialysis" with the purpose of establishing the level of cognitive impairment of the patient who performs hemodialysis, it is also investigated about the cognitive abilities presented and they are affected, through a psychological evaluation to improve their living conditions. The information obtained was through psychological techniques and tools that helped in the process of this case, among them are; the medical history, the interview, the observation and the May test, with the purpose of analyzing and understanding the problem in a better way. The results that were obtained are similar to the case study, in the same way the conclusion reached is that the identified patient in which this work has been performed, has a mild cognitive impairment, where their cognitive functions are affected such as memory, attention and information retention, a therapeutic scheme will be provided to improve the life condition of it.